Density regulation of aquaculture production and its effects on commercial profit and quality as food in the cosmopolitan edible seaweed Undaria pinnatifida - Sato, Yoichi; Fujiwara, Takayuki; Endo, Hikaru (Frontiers in Marine Science, 2023)
Aquaculture of marine macroalgae (i.e. seaweeds) such as the kelp Undaria pinnatifida is expected to contribute to future food and biomass production. Although macroalgal survival, biomass, and morphology are strongly affected by the density of individual plants in natural environments, little is known about the cultivation density (individuals per 1 m of cultivation rope) of macroalgae required to optimize aquaculture production, commercial profit (sales – labor expenses for processing), and quality as food. The present study examined the effect of increasing the cultivation density of U. pinnatifida from 10 to 200 individuals m-1 on survival rate, biomass production, profit, and morphological features related to quality as food. Survival rate was almost 100% in all treatments, indicating self-thinning did not occur. Biomass production increased with increasing density, suggesting that the maximum density possible is in excess of 200 individuals m-1. However, although profit rose with increasing density from 10 to 120 individuals m-1, it did not rise further if density was further increased. Moreover, some morphological features related to quality increased or decreased with increasing density. On balance, these results suggest that 80-120 individuals m-1 is an appropriate density range to optimize production of this species in terms of both profit and quality as food. However, only 10-30 individuals m-1 was the density best suited to enhance production of the sporophyll form, which is known to be a nutritious food both for humans and sea urchins.